Farming characteristics and self-reported health outcomes of Irish farmers. (17th February 2018) - van Doorn, D; Richardson, N; Storey, A; Osborne, A; Cunningham, C; Blake, C; McNamara, J
Abstract: Background: Irish farmers represent a 'high-risk' group for non-communicable diseases, which, arguably, pose a greater occupational health challenge for farmers. To date, there has been little exploration of the farming characteristics associated with farmers' poor health outcomes. Aims: To examine the relationship between farming and male farmers' self-reported health outcomes and to compare the study findings to national health studies to explore which factors specifically are associated with Irish farmers' poorer health outcomes relative to the general population. Methods: This cross-sectional survey research used self-reported quantitative data on the health outcomes and health behaviours of male farmers from the South-East of Ireland. Data were entered into SPSS and descriptive and binary regression techniques were used for data analysis. Results: There were 314 participants (99% response rate). Age, full-time farming and dairy farming significantly impacted self-reported health outcomes and health behaviours. There was a high prevalence of self-reported arthritis compared with the national average of Irish males. 'Younger' farmers (<45 years) were more likely to engage in harmful health behaviours such as smoking and 'binge-drinking' one or more times per week. Conclusions: This study identified self-reported patterns of risky lifestyle behaviours among particular subgroups of Irish farmers for whom targeted health interventions are warranted. Interventions are particularly important for younger farmers who may see themselves as invincible and impregnable to ill-health.